دراسة الحساسية السمية لثلاث متعضيات مائية تمثل المجموعات الرئيسة الثلاث للعوالق الحيوانية(Cladocera, Copepoda, Rotifera) في المياه العذبة اتجاه المبيد الحشري كلوربيريفوس - سابا, ميشيل (Latakia University Journal -Biological Sciences Series, 2016)
أجريت اختبارات السمية الحادة للمبيد الحشري كلوربيريفوس لتحديد متوسط التركيز القاتل النصفي LC50 خلال فترة تعرض 48 ساعة على ثلاثة أنواع من العوالق الحيوانية هي : Brachionus calyciflorus من الدوارات Rotifera، والميزوسيكلوب Mesocyclops leuskarti من مجذافيات الأرجل Copepoda والدافنيا Daphnia magna من متفرعات القرون Cladocera .وقد تبين أن النوع Daphnia magna هو الأكثر حساسية للمبيد كلوربيريفوس حيث بلغت قيمة 48h-LC50 = 1.28 µg/L ، يليه النوع Mesocyclops leuskarti 48h-LC50 = 28 µg/L ، بينما لوحظ ضعف شديد في حساسية النوع Brachionus calyciflorus اتجاه المبيد 48h-LC50 = 910 µg/L .واعتماداً على قيم الوحدات السمية TU فقد تبين أن سمية المبيد كلوربيريفوس هي من المستوى الرابع = عالي السمية (TU= 78.30) بالنسبة للDaphnia ، ومن المستوى الثالث = حاد السمية (TU= 3.57) بالنسبة لل Mesocyclops ، بينما هو من المستوى الأول = عديم السمية (TU= 0.11) بالنسبة للدواري Brachionus .وقد تبين أن كل زيادة في تركيز المبيد واحد ميكروغرام بالليتر تزيد معدل النفوق في أفراد جماعة النوع المدروس حوالي : Daphnia magna 68.79 % ، Mesocyclops leuskarti 0.22 % ، Brachionus calyciflorus 0.0468 % وبالنتيجة يمكن أن نتوقع أن وصول المبيد إلى النظم البيئية المائية سوف يؤثر على المجتمع الحيوي في هذه النظم وعلى جملة العلاقات القائمة فيه وهذا بدوره من الممكن أن يكون سبباً لاختلال التوازن البيئي مع عواقب مبهمة من الصعب إدراك ابعادها.Acute toxicity of the pesticide Chlorpyrifos tests were conducted to determine the Lethal concentration LC50 during 48 hours exposure on three species of fresh water Zooplankton: Brachionus calyciflorus ( Rotifera), Mesocyclops leuskarti (Copepoda) and Daphnia magna ( Cladocera).• It was found that the species Daphnia magna is the most sensitive to the pesticide Chlorpyrifos as the value of 48h-LC50=1.28 μg/L, followed by the species Mesocyclops leuskarti 48h-LC50=28 μg/L while it was observed severe lack of sensitivity of the species Brachionus calyciflorus to the pesticide 48h-LC50=910 μg/L.• Depending on the values of the units of toxicity TU has been shown that the toxicity of the pesticide Chlorpyrifos is from the fourth level = highly toxic (TU = 78.30) for Daphnia, and Level III = acute toxicity (TU = 3.57) for Mesocyclops, while it is the first level = non toxic (TU = 0.11) for Brachionus.• Each increase in the concentration of the pesticide 1.0µg/L lead to increase the mortality rate in the species studied about: Daphnia magna 68.79 % ، Mesocyclops leuskarti 0.22 % ، Brachionus calyciflorus 0.0468 % As a result, we can expect that the arrival of the pesticide to aquatic ecosystems will affect the whole bio-community in these ecosystems and the inter their relationships, which in turn could be the cause of the disruption of the ecological balance with vague consequences that are difficult to understand its dimensions.